Estudo estrutural e espectroscópico de íons lantanídeos contendo o carboxilato N-acetilglicina - Silva, Heberton Eugênio de Oliveira (2018)
In this work, the synthesis, characterization, and investigation of luminescent properties of compounds containing the carboxylate N-acetylglycine (AcGly) ligand coordinated to the trivalent lanthanide ions are reported. The characterization of the compounds was performed by complexometric titration with EDTA, infrared spectroscopy, proton nuclear magnetic resonance (1H NMR) and thermal analyzes (TG / DTG and DTA). The obtained data indicate that the obtained compounds present general molecular formula [Ln (AcGly)3(H2O)3], where Ln: Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb. The spectral absorption data in the infrared region showed values of Δν (wavenumber difference between the symmetrical and asymmetric stretches of the carboxylate group), around 100 cm-1, indicating that the AcGly ligands are coordinated to the Ln3+ ions in a bidentate chelating form via their carboxylate groups. The thermogravimetric analysis shows that all the water molecules are coordinated to the central metal ion and at the end of the analysis the lanthanide oxides are formed. X-ray diffraction analyzes showed that the compounds are all isomorphic. The luminescence (excitation and emission) spectra of the compounds, either in the visible or near infrared region, are characterized by narrow bands originating from intraconfiguration-4fn transitions centered on lanthanide ions. The Eu(AcGly)3(H2O)3 complex exhibits a spectral profile characteristic of a chemical environment of C3 symmetry. The values of intensity parameters, radiative and nonradiative rates and quantum efficiency for this complex were determined. Although there are no chromophores in its structure, the europium and terbium complexes exhibited luminescence from direct excitation. Furthermore, the terbium complex showed intense fractoluminescence at room temperature.